Effects of Chemical Modification and Ratio of Dragon Fruit (Hylocereus polyhizus) Peel Extract on The Dyed-Arrowroot (Maranta arundinacea) Starch - Harni, Mimi; Anggraini, Tuty; Rini, Rini; Suliansyah, Irfan (Green Engineering Society, 2023)
Color is the main attraction in choosing food; therefore, manufacturers do various ways to produce good colors without considering the consumer's health. Natural colors are a safe choice for health; besides being safe, natural dyes can also provide functional properties to those who consume them. The study aimed to determine the activity of natural dyes and their functional properties when mixed with chemically modified arrowroot starch. This study used a factorial design with chemical modification factor A and factor B, a ratio of dragon fruit extract to the amount of starch, with three repetitions. The best treatment was A2B3 (cross-link, starch with dragon fruit 1:2) because it had the treatment with the most visible color. This treatment has an antioxidant content of 38.95%, a polyphenol content of 106.19 mg GAE/g, a color of 76.88, and an anthocyanin content of 0.71 mg/100g.